Współczesne wyzwania dla integrującej się Europy. Problem pakietu klimatyczno-energetycznego i zaopatrzenia w surowce energetyczne. - Wiśniewska, Dorota (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
The aim of this article is to highlight a major evolving problem that the European Union has long been facing: energy deficiency. The article also illustrates a long and difficult process of integrating the energy sector. The process has to this day remained problematic one due to the fact that energy availability affects a country’s economic standing. Apart from that, EU member states have started seeking alternative sources of energy. These factors combined have prevented countries from reaching a consensus about climate and energy package. To conclude, this article not only presents the main advantages and disadvantages of climate-energy package, but also lists several possible solutions for the energy deficiency problem, which are quite novel in the field.